2001
DOI: 10.1046/j.1523-1755.2001.060002553.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolality activates Akt and regulates apoptosis in renal tubular cells

Abstract: The Akt pathway is activated by hyperosmolality in vitro and in vivo, and activation of Akt prevents the mild hyperosmolality-induced apoptotic changes in MDCK cells. PI3-K/Akt pathways are involved in a hypertonic condition that confers the balance between cell survival and apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
73
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 29 publications
10
73
1
1
Order By: Relevance
“…Proteins were separated on 7.5% or 10 -20% polyacrylamide gels and transferred to nitrocellulose membranes. Membranes were blocked for 1 h with 5% (wt/vol) fat-free milk in PBS and probed with the appropriate primary antibodies [anti-LC3 (MBL, RT-PCR analysis of RNA extracted from kidneys was carried out as previously described (39). In brief, total RNA was isolated from renal tissues using TRI-REAGENT (Life Technologies, Gaithersburg, MD).…”
Section: Induction Of Akimentioning
confidence: 99%
See 2 more Smart Citations
“…Proteins were separated on 7.5% or 10 -20% polyacrylamide gels and transferred to nitrocellulose membranes. Membranes were blocked for 1 h with 5% (wt/vol) fat-free milk in PBS and probed with the appropriate primary antibodies [anti-LC3 (MBL, RT-PCR analysis of RNA extracted from kidneys was carried out as previously described (39). In brief, total RNA was isolated from renal tissues using TRI-REAGENT (Life Technologies, Gaithersburg, MD).…”
Section: Induction Of Akimentioning
confidence: 99%
“…Caspase-3 assay and TUNEL assay. A Caspase-3 Fluorometric Protease Assay Kit (MBL) was used for the measurement of caspase-3 activity, as previously described (39). In brief, cell lysates were incubated with reaction buffer and 50 mM caspase-3 substrate for 2 h at 37°C, and the enzymatic activity was measured colorimetrically.…”
Section: Induction Of Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concluded that hypertonicity activates Akt͞PKB, including direct measurements of increased Akt͞PKB activity in NIH 3T3 and CHO cells (25). Also, phosphorylation of Akt͞PKB at S174 increases in MadinDarby canine kidney cells subjected to high NaCl and in inner medullas of rats subjected to dehydration (16). In contrast, other studies concluded that Akt͞PKB actually is inactivated by hypertonicity, including that high sorbitol decreases Akt͞PKB activity in HEK293 and COS cells (26) and that high sucrose decreases it in Swiss 3T3 cells, despite increased PIP3 abundance and increased PI3K activity (19).…”
Section: Relation Between Protein Kinases Involved In High Nacl-depenmentioning
confidence: 99%
“…Taken together, these findings suggest that other wortmannin-inhibitable kinases in addition to ATM contribute to high NaCl-induced activation of TonEBP͞ OREBP. PI3K seemed a likely candidate because high NaCl activates it, as reflected by the increase in phosphorylation (15,16) and activity (15) of its downstream target, AKT͞PKB. Further, high NaCl increases phosphorylation GSK-3␤ in renal medullary interstitial cells (17), which is significant because GSK-3 is a downstream target of PI3K (18) and phosphatidyl inositol 3-phosphate (PIP3) in Swiss 3T3 cells (19).…”
mentioning
confidence: 99%